2013
DOI: 10.1167/tvst.2.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Towards Patient-Tailored Perimetry: Automated Perimetry Can Be Improved by Seeding Procedures With Patient-Specific Structural Information

Abstract: Purpose: To explore the performance of patient-specific prior information, for example, from structural imaging, in improving perimetric procedures. Methods:Computer simulation was used to determine the error distribution and presentation count for Structure-Zippy Estimation by Sequential Testing (ZEST), a Bayesian procedure with prior distribution centered on a threshold prediction from structure. Structure-ZEST (SZEST) was trialled for single locations with combinations of true and predicted thresholds betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…26,27 However, the implementation of recommendations for increased frequency of testing has been challenging, with issues of timing and availability of resources being cited as barriers, despite long-term cost savings. 28 Alternative approaches, such as the use of previous sensitivity information, 29 adaptation to regions of interest, such as scotomata, 30 censoring of unreliable test points to reduce the number of stimulus presentations, 31 and the use of structural information for targeting specific regions of the visual field 32,33 remain theoretical at present and have not yet been widely implemented in practice.…”
mentioning
confidence: 99%
“…26,27 However, the implementation of recommendations for increased frequency of testing has been challenging, with issues of timing and availability of resources being cited as barriers, despite long-term cost savings. 28 Alternative approaches, such as the use of previous sensitivity information, 29 adaptation to regions of interest, such as scotomata, 30 censoring of unreliable test points to reduce the number of stimulus presentations, 31 and the use of structural information for targeting specific regions of the visual field 32,33 remain theoretical at present and have not yet been widely implemented in practice.…”
mentioning
confidence: 99%
“…This can be achieved by making predictions of sensitivity at each visual field location based on OCT measurements as mentioned, and then using these predictions as a starting point for testing the visual field. Denniss et al took this approach, using a modified Zippy Estimation by Sequential Testing procedure with Gaussian prior probability mass function centred on hypothetical predictions from structural data to investigate the possibility of improving visual field sensitivity measurements in this way. The study showed that the procedure seeded by predictions from structural measures could deliver benefits over existing procedures when the structure‐derived predictions of visual field sensitivity were accurate to within ±9 dB .…”
Section: Potential Use Of Oct To Predict Visual Field Thresholds or Tmentioning
confidence: 99%
“…Denniss et al took this approach, using a modified Zippy Estimation by Sequential Testing procedure with Gaussian prior probability mass function centred on hypothetical predictions from structural data to investigate the possibility of improving visual field sensitivity measurements in this way. The study showed that the procedure seeded by predictions from structural measures could deliver benefits over existing procedures when the structure‐derived predictions of visual field sensitivity were accurate to within ±9 dB . Similar advantages over existing visual field test procedures were demonstrated by Ganeshrao et al, who incorporated structure‐based predictions of visual field sensitivity into a combined suprathreshold‐threshold procedure.…”
Section: Potential Use Of Oct To Predict Visual Field Thresholds or Tmentioning
confidence: 99%
“…In clinical practice, the reliability of SAP results is affected by a range of factors, including those that are patient‐related. Modern thresholding algorithms have been developed to increase test efficiency and reduce patient fatigue (see McKendrick for a full review and select recent papers for newer algorithms). The reliability of the visual field results can be assessed using four primary indices or some variation thereof: fixation losses, false positives, false negatives and the results of gaze tracking.…”
Section: Standard Automated Perimetry In Clinical Practicementioning
confidence: 99%
“…52 In clinical practice, the reliability of SAP results is affected by a range of factors, including those that are patient-related. Modern thresholding algorithms have been developed to increase test efficiency and reduce patient fatigue (see McKendrick 53 for a full review and select recent papers for newer algorithms [54][55][56] A key for the greyscale levels of probability of normality is shown as an inset. (A) The right eye findings of a 54-year-old Asian man with moderate normal-tension glaucoma.…”
Section: Automated Perimetry In Clinical Practicementioning
confidence: 99%